2022
DOI: 10.1186/s12889-022-13027-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with COVID-19 vaccine intent among Latino SNAP participants in Southern California

Abstract: Background COVID-19 is significantly impacting the health and well-being of the country, particularly for ethnic minority populations and low-income groups. Our goal was to determine COVID-19 vaccination intent in a low-income, Latino population receiving aid from the Supplemental Nutrition Assistance Program (SNAP) in Southern California, and identify contributing factors and concerns. Methods A cross-sectional, mixed-methods survey was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…Consistent with prior studies on parental health beliefs, resistant parents were more likely than the unsure and accepting parents to hold COVID-19 vaccine misconceptions, believe their child was not susceptible to infection, that COVID-19 symptoms would be less severe, that the vaccine would be harmful to their child and unnecessary, and hold higher levels of general vaccine mistrust [ 9 , 12 , 23 , 24 , 25 , 54 ]. COVID-19 vaccine misinformation, conspiracy theories and hoaxes have been pervasive in the general mass media as well as in social media posts specifically targeting Hispanic communities [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with prior studies on parental health beliefs, resistant parents were more likely than the unsure and accepting parents to hold COVID-19 vaccine misconceptions, believe their child was not susceptible to infection, that COVID-19 symptoms would be less severe, that the vaccine would be harmful to their child and unnecessary, and hold higher levels of general vaccine mistrust [ 9 , 12 , 23 , 24 , 25 , 54 ]. COVID-19 vaccine misinformation, conspiracy theories and hoaxes have been pervasive in the general mass media as well as in social media posts specifically targeting Hispanic communities [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 72%
“…In national studies that included samples of Hispanic respondents, application of the health beliefs model (HBM) and related theories of planned health behaviors [ 17 , 18 , 19 , 20 ] indicate that the most consistent predictors of parental intentions for COVID-19 vaccine uptake for children were misinformation, underestimation of disease severity and susceptibility, distrust of vaccine safety and efficacy, a lack of community support for vaccinating children against infection [ 9 , 10 , 11 , 12 ], lower income and education, and lack of private insurance [ 17 , 18 , 21 , 22 ]. These factors have also been identified among Hispanic parents as predictive of routine and influenza pediatric vaccination intent [ 21 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to pregnant women, postpartum women reporting ever receiving an influenza vaccine remained a statistically significant predictor of maternal and child COVID-19 vaccination intent in all adjusted models which is consistent with prior studies [17,34,37,67]. Overall, the findings from this study suggest that targeting women with influenza vaccination history may be a crucial part of increasing vaccination uptake among pregnant and postpartum women regardless of race/ethnicity [70,71]. These findings also have implications for researcher and clinicians considering approaches that involve coadministration of influenza and COVID-19 vaccinations.…”
Section: Discussionsupporting
confidence: 87%
“…Both infertility and concerns about a chip being implanted were reported in another qualitative study with Hispanic families [ 25 ], although the study did not report if participants were vaccinated. Scott and colleagues (2022) found that fear of chip insertion was a barrier to vaccination among Hispanic females; yet approximately half of the study participants reported intent to vaccinate against COVID-19 [ 26 ]. Concerns about the safety and myths and misconceptions of the COVID-19 vaccine were the top two reasons that unvaccinated participants were hesitant in a national survey with 225 Hispanic adults [ 27 ].…”
Section: Discussionmentioning
confidence: 99%